Molecular and genetic basis of resistance to Russian wheat aphid (Diuraphis noxia) - Sharma, Vinod, author; Lapitan, Nora L. V., advisor; Haley, Scott D., committee member; Peairs, Frank B., committee member; Vivanco, Jorge M., committee member (Colorado State University. Libraries, 2005)
The Russian wheat aphid (Diuraphis noxia, RWA) is a pest of wheat (Triticum aestivum L.), barley (Hordeum vulgare L.), and rye (Secale cereale L.). It has caused serious economic damage to wheat and barley growers all over the world. RWA infestation results in leaf rolling, streaking of the leaves, leaf and head trapping, stunted growth of the plants and even death of susceptible plants. Under heavy infestation it can cause a yield reduction of 50% or more. The use of resistant cultivars is an efficient, economical and environmentally safe method to protect small grain cereals from losses by RWA. Until spring 2003 there was only one RWA biotype (biotype 1) found in N. America. In spring of 2003 another RWA biotype (biotype 2) was reported from Colorado and other wheat growing states. This biotype was found to be virulent to all known RWA resistance genes except for Dn7. Dn7 is a dominant resistance gene which was introduced into wheat from rye by 1BL.1RS translocation. It provides superior level of resistance against both RWA biotypes. The objectives of this study were: 1) Saturation mapping of a gene-rich region in rye chromosome arm 1RS, containing a Russian wheat aphid resistance gene Dn7, 2) To find out if there is synteny between region of short arm of rye chromosome 1RS containing Dn7 and rice, and 3) In-vitro reaction of wheat to extracts of Russian wheat aphid biotypes 1 & 2. F2 derived F3 families of a cross between wheat line '94M370' (resistant to RWA containing DnT) and wheat cy 'Gamtoos' (susceptible to RWA) were advanced to the F6 generation by single seed descent. DNA polymorphisms were detected in 98 recombinant inbred lines (RILs) with restriction fragment length polymorphism (RFLPs), expressed sequence tags (ESTs), amplified fragment length polymorphism, simple sequence repeats (SSRs), resistance gene analogs (RGAs) and sequence tagged sites (STS) markers. To find out if there is a synteny between 1RS region containing Dn7 and rice genome, DNA sequences of the markers linked to Dn7 were used to do BLAST homology searches with the rice sequence databases. For in vitro studies, cut etiolated seedlings of RWA resistant and susceptible cultivars were treated with crude extract, saliva, proteins, and non protein compounds of RWA biotypes 1 and 2. The present genetic map of 1RS contains twenty six DNA markers covering a genetic distance of 97.5 cM. The markers flanking the Dn7 are XHor1 and XIb267 which are 2.1 and 3.9 cM from Dn7, respectively. Nine PCR-based markers were developed for Dn7. One AFLP fragment linked to Dn7 was successfully converted to high-throughput STS marker. This is the first time PCR-based markers have been developed for Dn7. Two PCR-based markers, XIb267 and Xrems1303_1, flanking the Dn7 gene had an accuracy of 96% when used for marker assisted selection for RWA resistance. No conserved homology was observed with rice chromosome 5 and 10 which are known to be homoeologous with the group 1 chromosomes of Triticeae when the rice BAC/PACS showing highest homology were selected. But three markers linked to Dn7 were found to be homologous with rice BAC/PACs from rice chromosome 1 (R1) when all the rice BAC/PACs having homology of E ≤ e-10 were selected. These BAC/PACs were aligned in the same order as markers in Dn7 linkage map. However this synteny between the regions of 1RS carrying Dn7 and rice genome was not able to provide additional markers for the Dn7 gene. Crude extract of RWA biotype 1 significantly inhibited leaf unrolling of susceptible cultivar 'Gamtoos' whereas had no significant effect on other two susceptible cultivars 'Carson' and 'Synthetic Hexapioid'. Crude extract of RWA biotype 2 significantly inhibited leaf unrolling of 'Carson' and 'Synthetic Hexapioid' but not of 'Gamtoos'. The data obtained from RWA saliva, proteins and non protein compounds were generally uninformative as few significant differences were observed between treatments and control. A dense genetic map of 1RS region can facilitate the map-based cloning of important disease and insect resistance genes which are present on short arm of rye chromosome 1RS. Also DNA makers developed for Dn7 in this study will help in marker assisted selection (MAS) for RWA resistance screening as 96% accuracy can be achieved for selecting a resistant line by using PCR markers flanking the Dn7. Although in vitro studies were generally uninformative, it lays the ground for further work to develop a bioassay for RWA resistance screening and also to find out the elicitors responsible for expression of resistance in RWA resistant cultivars.
Keywords: agronomy; plant propagation; plant sciences